Menjembatani Teori dan Praktik: Tinjauan Naratif Early Clinical Exposure dalam Pendidikan Kedokteran Tahap Pre-Klinik - Josephine, Jodie (Universitas Kristen Krida Wacana, 2026)
Early Clinical Exposure (ECE) has become an essential component of integrated medical curricula, aiming to bridge the long-standing divide between basic science teaching and clinical practice. This narrative review synthesised fourteen studies published in the past five years to examine the educational rationale, implementation models, and outcomes of ECE for undergraduate medical students. Evidence shows that ECE enhances integration of basic and clinical sciences, strengthens motivation, and supports early professional identity formation. Students also gain confidence and foundational clinical skills when ECE includes structured supervision and opportunities for guided practice. Different implementation models, hospital-based, classroom-integrated, community-based, and hybrid, offer distinct benefits aligned with specific learning mechanisms. However, substantial variability in programme design, supervision quality, and learning environments contributes to inconsistent outcomes. Common barriers include large cohort sizes, limited clinician availability, overcrowded clinical settings, and reliance on brief or observational exposure. These issues highlight a persistent gap between the strong theoretical foundations of ECE and its uneven practical execution. Optimising ECE requires intentional, longitudinal design; structured reflection; adequately prepared supervisors; and alignment with experiential, social, and contextual learning principles. When effectively implemented, ECE can serve as a transformative element of early medical training.